Proceedings of the 13th International Conference on Multimodal Interfaces 2011
DOI: 10.1145/2070481.2070533
|View full text |Cite
|
Sign up to set email alerts
|

Perceived physicality in audio-enhanced force input

Abstract: This paper investigates how the perceived physicality of the action of applying force with a finger on a rigid surface (such as on a force-sensing touch screen) can be enhanced using real-time synthesized audio feedback. A selection of rich and evocative audio designs was used. Additionally, audio-tactile cross-modal integration was encouraged, by observing that the main rules of multisensory integration were supported. The study conducted showed that richness of perceived physicality increased considerably, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In their study, participants felt an isometric input device as a compliant one when they used it while looking at a virtual spring on the screen. Lai et al [21] showed a possibility that sound feedback in response to a force change can create a compliance illusion on a rigid surface without using other modalities. As we mentioned earlier, there have been many studies where a short vibrotactile feedback was used to create the illusion of pressing a button [3]- [8].…”
Section: A Compliance Illusion Methodsmentioning
confidence: 99%
“…In their study, participants felt an isometric input device as a compliant one when they used it while looking at a virtual spring on the screen. Lai et al [21] showed a possibility that sound feedback in response to a force change can create a compliance illusion on a rigid surface without using other modalities. As we mentioned earlier, there have been many studies where a short vibrotactile feedback was used to create the illusion of pressing a button [3]- [8].…”
Section: A Compliance Illusion Methodsmentioning
confidence: 99%
“…It has also been used to convey information in order to reduce visual load or when vision is occupied. Furthermore, sound has been used to provide cross-modal feedback [2] or to enhance and alter the perceived physicality of a rigid surface [18]. Moreover, the capabilities of sonification for teaching gestures and providing feedback in learning process has been studied [1,21].…”
Section: Related Workmentioning
confidence: 99%
“…It has been found that audio and tactile augmentation can separately enrich the perceived physicality of voluntary actions performed with the hands [9,10], and they can support visual navigation in physical space, for example, in searching objects [14].…”
Section: Background and Related Workmentioning
confidence: 99%
“…With regards to the specific experiences of audio in AHNE, the sound behaviour was experienced as logical and natural (easy and comprehensible) (10). Nine participants said that the sounds told something about their distance to the objects and helped with finding them.…”
Section: User Experience Of Audio and Tactile Feedbackmentioning
confidence: 99%